Luminous bacteria in two species of leiognathids, Leiognathus splendens and L. bindus* - Sivasankar, N; Jayabalan, N (Indian Journal of Fisheries, 2011)
Luminous baceria in 2 species of ponyfishes Leiognathus splendens and L. bindus were studied.The log number of luninous bacteria in L. splendens ranged from 9.0560 to 10.1688 per gram wet weightof light organ. L. bindus the values ranged from 9.1105 to 10.1600 per gram wet weight of thelight organ.The percentage contribution of bacteria to the weight of the light organ ranged between 2.27% and 29.4%in L. splendens and 2..'i8% and 28.91 % in L. bindus respectively. There seems to be a definite relationshipbetween the size of ths organ and the number of bacterial cells